Exploring Online Sentiment (OS) As a Measure of Customer Experience (CX) for Telecommunication Services. Issue 3 (3rd July 2022) - Lappeman, James; Meyer, Seth; Miguel, Diana
Abstract: In this study, online sentiment (OS) was used to explore customer experience (CX) for the telecommunications industry. There is no agreed standard for CX measurement with many challenges in metrics like Net Promoter Score (NPS). The study explored the CX of the UK's four biggest consumer-facing telecommunications companies by isolating CX from brand perception sentiment, tracking sentiment along the customer journey and observing CX across platforms. The findings show that CX sentiment can be isolated from brand perception and that customer satisfaction levels change along the customer journey. In addition, CX sentiment also differs between service channels.